The Development of Qur'anic Interpretation in the Era of Reformation in Indonesia - Dr. Muhammad Arifin S.H., M.Hum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
By exploring some works of Tafsir thoese were published in 2000s until oresent, the writer aconcludes that the development of Qur'anic interpretation in the reformation era is a continuation of the paradigm in the1990s.